SCHOOL AND COMMUNITY RELATIONSHIP: Comparative Study of Law Number 20 Year 2003 - Aidil Saputra (Jurnal Ilmiah Teunuleh, 2021)
Education is an attempt to change a person's circumstances from not knowing to knowing, from not being able to do to being able to do, from not acting as expected to being as expected.. Aninstitution designed for the teaching of students or students under the supervision of educators (teachers). Society is an embodiment of life with man. In society, the process of social life is the process between relationships and interactions. Society as an institution of human life also takes place the whole development of human life. Community can be interpreted as a container or terrain where the interaction of community citizens takes place. All of these are national programs that have been researched and studied for truth. In the past, schools had pluses at high status. People who are highly respected and respected schools, teachers are respected by learners and the community. In addition, the School is a formal educational institution that has an important role in developing scientific insights to every citizen who will hold education. Therefore, to make the school as one of the educational institutions requires good management of the entire academic community and get support from the community and government.